If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 + -6x = -15 Reorder the terms: -12 + 3x + -6x = -15 Combine like terms: 3x + -6x = -3x -12 + -3x = -15 Solving -12 + -3x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -3x = -15 + 12 Combine like terms: -12 + 12 = 0 0 + -3x = -15 + 12 -3x = -15 + 12 Combine like terms: -15 + 12 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 7x-2=4x-9 | | -90=9 | | 3x+3x+3+3=24 | | 3(d+9)=-12 | | 260x=0.13 | | 2x+2.5x-8+2=3 | | -y^8-2=-5 | | -18=v-(-2) | | 0.13x=260 | | 260x=13 | | 1/3(6-9h)=h/3-6 | | 6x-1/3=12 | | 2-9n=16 | | m/2-8=12 | | -8b=4/9 | | 2/3x+16=36 | | 17+k=12 | | (d/12)=2 | | x/5+2=x/3+14 | | 10=24-7x | | x/2+x+x/3=5 | | y=x^2+12x+20 | | 5g+6-2=4g+4+g | | 2/3x+16=38 | | 2(x-1)+4(x-3)=9 | | 6*0-4y=-20 | | 2c(c+3)=c-13 | | 6x^2+7x-10/4x+8 | | P+4=22 | | 3y-12=128 | | 2/25x=10 | | y=x^2-8x-48 |